2002
DOI: 10.1002/ejsp.112
|View full text |Cite
|
Sign up to set email alerts
|

Psychological effects of the Euro—experimental research on the perception of salaries and price estimations

Abstract: In five studies we show that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
55
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 39 publications
(50 reference statements)
3
55
1
Order By: Relevance
“…However, the illusion was weaker or absent when low-priced essential goods or services were rated or when a negative mood was induced. Other experimental studies have reported related findings, for example, when evaluative judgements were expressed as price estimates (Jonas, Greitemeyer, Frey, & Schulz-Hardt, 2002), or as willingness to pay judgements (Raghubir & Srivastava, 2002), or as importance ratings for gains and losses (Tyszka & Przybyszewski, 2003).…”
Section: Attitudes and Feelingsmentioning
confidence: 85%
“…However, the illusion was weaker or absent when low-priced essential goods or services were rated or when a negative mood was induced. Other experimental studies have reported related findings, for example, when evaluative judgements were expressed as price estimates (Jonas, Greitemeyer, Frey, & Schulz-Hardt, 2002), or as willingness to pay judgements (Raghubir & Srivastava, 2002), or as importance ratings for gains and losses (Tyszka & Przybyszewski, 2003).…”
Section: Attitudes and Feelingsmentioning
confidence: 85%
“…For instance, slicing up a pizza into several pieces affects the estimated food quantity when the pieces are removed from the plate and displayed horizontally but not when they are left on the plate so that they still form the pizza (Pelham et al,study 1). Similarly, the (reverse) face-value effect seems limited to situations in which consumers are unfamiliar with the unit of measure (Jonas et al 2002;Raghubir and Srivastava 2002). To the extent that a consumer becomes familiar with a foreign currency, this difference disappears (Marques and Dehaene 2004).…”
Section: Further Research and Implicationsmentioning
confidence: 99%
“…Participants in the immoral condition thought they could purchase fewer items than participants in the neutral condition. Their study demonstrates that perceptions of money's value depend on a situational factor that is logically unrelated to how much money can actually buy (see also Dubois, Rucker, and Galinsky 2012;Jonas, Greitemeyer, Frey, and Schulz-Hardt 2002;Lasaleta, Sedikides, and Vohs 2014;Wertenbroch, Soman, and Chattopadhyay 2007). Going beyond this past work, we examine whether perceptions of money's value depend on to whom the money belongs.…”
mentioning
confidence: 96%